TANGGUNG JAWAB YURIDIS PT.ADIRA FINANCE SAMARINDA TERHADAP KORBAN TINDAKAN LAPPING COLLECTOR BERDASARKAN UU NO.8 TAHUN 1999 - Krisna Bayu Pratama (Journal of Law ( Jurnal Ilmu Hukum ), 2015)
ABSTRACTConsumer protection issues are things to note, consumer rights are ignored by businesses needs to be examined thoroughly one of the actions that could harm consumers lapping is performed collector leasing. To protect consumers leasing actually not rely solely on the application of civil law as expected through the mechanism of sanctions and lawsuits for damages. The current state of consumer protection has received serious attention to the enactment of laws and regulations governing, namely Law No. 8 of 1999 on Consumer Protection. Nevertheless, you still need a caution in determining who is responsible for omissions or mistakes by the leasing resulting in a loss experienced by consumers. In writing this essay the author using normative juridical method that describe the facts or symptoms with the lapping action collector.Results of the study authors in the field based on real conditions that exist, then on this thesis illustrates that PT.Adira Finance in this case as the business communities establish that everything is charged to the consumer could be eliminated and still provide sanctions to Biller which in this case is the collection with reference to the provisions under Law Protection consumers are regulated in Article 19 paragraph (1) and (2).___________________________________________Keywords: lapping collector and consumer protection.